Molecular Influence of Anterior Cruciate Ligament Tear Remnants on Chondrocytes: A Biologic Connection between Injury and Osteoarthritis - Chinzei, Nobuaki (Osteoarthritis Cartilage, 2018)
OBJECTIVE: Anterior cruciate ligament (ACL) injury initiates a cascade of events often leading to osteoarthritis. ACL reconstruction does not alter the course of osteoarthritis, suggesting that heightened osteoarthritis risk is likely due to factors in addition to the joint instability. We showed that torn ACL remnants express periostin (POSTN) in the acute phase of injury. Considering that ACL injury predisposes to osteoarthritis and that POSTN is associated with cartilage metabolism, we hypothesize that ACL injury affects chondrocytes via POSTN. DESIGN: Cartilage was obtained from osteoarthritic patients and ACL remnants were collected from patients undergoing ACL reconstruction. Crosstalk between remnants and chondrocytes was studied in a transwell co-culture system. Expression of POSTN and other anabolic and catabolic genes was assessed via real-time PCR. Immunostaining for periostin was performed in human and mouse cartilage. The impact of exogenous periostin and siRNA-mediated ablation of periostin on matrix metabolism and cell-migration was examined. Furthermore, the effect of anabolic (TGF-β1) and catabolic (IL-1β) factors on POSTN expression was investigated. RESULTS: ACL remnants induced expression of POSTN, MMP13 and ADAMTS4. Periostin levels were significantly higher in osteoarthritic compared to normal cartilage. Exogenous periostin induced MMP13 expression and cell-migration, repressed COL1A1 expression while POSTN-knockdown inhibited expression of both anabolic and catabolic genes and impeded cell-migration. TGF-β1 and IL-1β treatment did not alter POSTN expression but influenced chondrocyte metabolism as determined by anabolic and catabolic genes. CONCLUSIONS: ACL remnants can exert paracrine effects on cartilage, altering cellular homeostasis. Over time, this metabolic imbalance could contribute to osteoarthritis development.